350 Incidence, severity and risk factors of retinopathy of prematurity in a tertiary care centre in Kerala. (17th August 2022) - Kuriakose, Mathews E; Zacharias, Rekha; Athira, R
Abstract : Aims: To study the incidence, severity and risk factors of ROP in neonates delivered in or referred to Neonatology and Paediatrics department of a tertiary care hospital in Kerala. Methods: STUDYAREA: Neonatology and Paediatric department of a tertiary care hospital, in Ernakulum, Kerala. STUDY POPULATION: Neonates delivered in the neonatology and paediatric department of a tertiary care centre in kerala satisfying the inclusion criteria. STUDY DESIGN: Hospital based retrospective cohortstudy. d. STUDY DURATION: From 01/01/2018 to 31/08/2021. DATA COLLECTION METHODS: The study was conducted among newborns satisfying the inclusion criteria were found from the electronic medical records (EMR) registry of department of Neonatology and Paediatrics of a tertiary care hospital at Kochi.56 samples were identified. Data was collected from the medical records using a standardised data collection chart, and analysed. Baseline data was collected for each baby regarding date of birth, sex, single or multiple pregnancies, intrauterine growth retardation and other antenataldetails DATA COLLECTION FORMS: Data collected using a standardised data collection chart and tabulated in Microsoft excel. Results: Incidence of ROP was found to be 21.4% (12/56) with higher proportion of neonates developing early stages of ROP. The incidence of ROP with a confidence interval of 95% by modified Waid method ranges from 12.5% to33.9%. The incidence of ROP in the present study is comparable to most of the national and internationalstudies. Maternal factors including PIH, GDM, Antenatal steroid administration, ante partum hemorrhage, delivery method and multiple gestations were not found to be associated with development of ROP. Neonatal risk factors including lower birth weight, lower gestational age, surfactant therapy, longer duration of oxygen requirement, anemia, blood transfusion, phototherapy and sepsis were found to be major risk factors for development ofROP. Conclusion: 1. Incidence of ROP was found to be 21.4% (12/56) with higher proportion of neonates developing early stages of ROP. 2. The incidence of ROP with a confidence interval of 95% by modified Waid method ranges from 12.5% to33.9%. 3. The incidence of ROP in the present study is comparable to most of the national and internationalstudies. 4. Most of the risk factors associated with ROP arise during the stay in neonatal intensive care unit and some of them are avoidable. The incidence of ROP can be decreased by monitoring the risk factors, timely screening, regular follow up and appropriate interventions. 5. References-Dr Rekha Zacharias MBBS MD email rekhajo@gmail.com, Dr Johny VF MBBS MD Email drjohnyvf@yahoo.com